Insights into the structure and architecture of the CCR4–NOT complex - Xu, Kun; Bai, Yuwei; Zhang, Aili; Zhang, Qionglin; Bartlam, Mark G. (Frontiers in Genetics, 2014)
The CCR4-NOT complex is a highly conserved, multifunctional machinery with a general role in controlling mRNA metabolism. It has been implicated in a number of different aspects of mRNA and protein expression, including mRNA degradation, transcription initiation and elongation, ubiquitination, and protein modification. The core CCR4-NOT complex is evolutionarily conserved and consists of at least three NOT proteins and two catalytic subunits. The L-shaped complex is characterized by two functional modules bound to the CNOT1/Not1 scaffold protein: the deadenylase or nuclease module containing two enzymes required for deadenylation, and the NOT module. In this review, we will summarize the currently available information regarding the three-dimensional structure and assembly of the CCR4-NOT complex, in order to provide insight into its roles in mRNA degradation and other biological processes.